1998
DOI: 10.4269/ajtmh.1998.58.406
|View full text |Cite
|
Sign up to set email alerts
|

IgG3 antibodies to Plasmodium falciparum merozoite surface protein 2 (MSP2): increasing prevalence with age and association with clinical immunity to malaria.

Abstract: In a cross-sectional survey carried out in west Africa (The Gambia), where Plasmodium falciparum malaria is endemic with seasonal transmission, 178 individuals 1-75 years of age were assessed for their antibody response to the malaria vaccine candidate, merozoite surface protein 2 (MSP2). Total IgG to recombinant antigens representing full-length, repetitive, and group-specific domains of both allelic families of MSP2 was determined by ELISA. The IgG-subclass profile of IgG-positive sera was assessed. Antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
166
3
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 34 publications
22
166
3
2
Order By: Relevance
“…Population genetic approaches can help to identify potential protective antigens (see above) but more direct approaches, such as immunoepidemiological studies of the association between a specific immune response to a particular antigen and susceptibility or resistance to clinical malaria, can also be used (Riley et al 1991, Al-Yaman et al 1994, Taylor et al 1998). We have recently completed an immunoepidemiological study designed to test whether anti-malarial antibodies transferred from mother to child across the placenta, can in fact protect neonates and infants from malaria infection or malaria disease.…”
Section: Mechanisms Of Immunity To Malariamentioning
confidence: 99%
“…Population genetic approaches can help to identify potential protective antigens (see above) but more direct approaches, such as immunoepidemiological studies of the association between a specific immune response to a particular antigen and susceptibility or resistance to clinical malaria, can also be used (Riley et al 1991, Al-Yaman et al 1994, Taylor et al 1998). We have recently completed an immunoepidemiological study designed to test whether anti-malarial antibodies transferred from mother to child across the placenta, can in fact protect neonates and infants from malaria infection or malaria disease.…”
Section: Mechanisms Of Immunity To Malariamentioning
confidence: 99%
“…The analysis is based on the evaluation of the presence and number of P. vivax merozoite surface protein-3␣ (PvMsp-3␣) alleles. 7 Proteins on the surface of Plasmodium merozoites are targets of naturally acquired [8][9][10] and vaccine-induced immunity against malaria. 11,12 The PvMsp-3␣ 7 is a member of an Msp3 gene family that is genetically related to P. falciparum merozoite surface protein-3 (PfMsp-3).…”
mentioning
confidence: 99%
“…The greater flexibility of the hinge region of IgG3 probably allows IgG3 to associate better with activating Fcγ receptors such as FcγRI and FcγRIIA [46,48,49] to mediate efficient bacterial uptake and the subsequent intracellular bacterial killing, possibly hence resulting in lower host cell death at 8 h p.i.. In fact, Th1-associated IgG3 has been shown to be more advantageous than the other subclasses in other infection systems, where IgG3 is negatively associated with progression of clinical diseases [50]. We have recently demonstrated that Th1-associated murine IgG2a and IgG2b were the most efficient isotypes at lowering Salmonella bacterial load in the blood, liver and spleen in vivo following infection in mouse [51].…”
Section: Discussionmentioning
confidence: 99%